Assessing the Determinants of Bank Interest Rate Spread: Evidence From Western Balkan Countries - Artor Nuhiu; Florin Aliu; Arbër Hoti (SAGE Open)
This study investigates the effect of macroeconomic and bank-specific factors on the bank interest rate spread (IRS) of six Western Balkan countries (referred to as WB6). We applied the Panel Vector Autoregression (Panel VAR) model to separately analyze the impact of these two sets of factors for 2005 to 2022 using two-panel datasets from 110 banks. The results from the two models show that the IRS is significantly influenced by GDP per capita and the unemployment rate, while other factors, such as bank concentration, performance indicators, and non-performing loans, show limited direct effects. The study identifies a notable gap in the existing literature by emphasizing how macroeconomic and bank-specific variables, particularly in transition economies, can simultaneously affect the IRS. The research highlights the distinctive financial dynamics within the WB6 countries and the relevance of comprehending the region’s banking sector characteristics. It contributes to academic and policy discussions on the significance of financial stability and market competitiveness in determining the bank IRS. The findings can be helpful for banking regulators and policymakers in the Western Balkans seeking to foster an efficient and competitive banking environment. JEL Classification: C33, E43, G21.